2006
DOI: 10.1007/s11661-006-0164-1
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ observations of oxidation and phase stability in cast nickel-based intermetallic alloys

Abstract: The effects of the as-cast microstructure on the oxidation characteristics of two Ni-Al-Cr alloys with either ␥ or ␥Ј primary solidification were investigated with an in-situ, time-resolved X-ray diffraction (TRXRD) technique using synchrotron radiation. The measurements, carried out during rapid heating and cooling, showed that a segregated microstructure in these cast alloys leads to the preferential formation of zirconium oxide before the formation of aluminum oxides is detected. The oxidation leads to a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Synchrotron experimental techniques based primarily on conventional X-ray diffraction techniques have been used recently by a number of experimentalists to track phase changes under isothermal and continuous heating conditions. [1][2][3][4][5][6][7][8] These studies have monitored phase transformations in copper, 1 steels, [2][3][4][5] titanium alloys 6,7 and nickel based alloys. 8 Even though these references do not form a comprehensive list, they provide an overview of the types of experiments being performed and the variety of phase transformations being studied using synchrotron X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrotron experimental techniques based primarily on conventional X-ray diffraction techniques have been used recently by a number of experimentalists to track phase changes under isothermal and continuous heating conditions. [1][2][3][4][5][6][7][8] These studies have monitored phase transformations in copper, 1 steels, [2][3][4][5] titanium alloys 6,7 and nickel based alloys. 8 Even though these references do not form a comprehensive list, they provide an overview of the types of experiments being performed and the variety of phase transformations being studied using synchrotron X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] These studies have monitored phase transformations in copper, 1 steels, [2][3][4][5] titanium alloys 6,7 and nickel based alloys. 8 Even though these references do not form a comprehensive list, they provide an overview of the types of experiments being performed and the variety of phase transformations being studied using synchrotron X-ray diffraction. However, these techniques are designed to examine phase transformations under isothermal or near isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…287 For example, this was observed in a cast Ni alloy with compositional heterogeneity by TRXRD with synchrotron radiation. 288 These measured kinetic can be interpreted with CT and CK models by calculating the oxygen activity and relating the same to the local phase stability conditions brought about by compositional heterogeneity.…”
Section: Microstructure Evolution During Weld Thermal Cyclingmentioning
confidence: 99%
“…291 In addition, the CT tools can be used to evaluate the tendency for the dissolution of oxides by evaluating the solubility constants of surface oxides. 288 In addition, the CT tools can be used to design understand selfpropagating exothermic reactions in nanolaminates used for microelectronics joining. The CT methodology for evaluating self-propagating exothermic calculations was outlined by Joslin et al 292…”
Section: Application To Solid-state Joiningmentioning
confidence: 99%
“…25 The addition of Cr element improves the material's corrosion resistance signicantly. 28 Our team has studied porous Ni-Cr-Fe cathode which shows signicant catalytic performance in 6 M KOH solution, the Tafel slope is À130 mV dec À1 , and the exchange current density is 7 Â 10 À4 A cm À2 at elevated temperature. 29 It is also found that Ni-Fe-C cathode owns benet of good catalytic activity and stability for HER, and the observed activity is mainly due to the intrinsic activity induced by carbon embedded into Ni-Fe matrix.…”
Section: Introductionmentioning
confidence: 99%